2021
DOI: 10.1002/ieam.4461
|View full text |Cite
|
Sign up to set email alerts
|

Framework for nontargeted investigation of contaminants released by wildfires into stormwater runoff: Case study in the northern San Francisco Bay area

Abstract: This article is part of the special series "Ecological consequences of wildfires." The series documents the impacts of largescale wildfires in many areas of the globe on biodiversity and ecosystem condition in both terrestrial and aquatic ecosystems, the capacity for systems to recover and management practices needed to prevent such destruction in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The features were then annotated with sample collection sites and storm events, and numbers of features for each sampling and reference sites are summarized in Table 1. No clear relationship was observed between overall numbers of features and levels of development or burned percentage (Supporting Information, Table S1), though in the companion study using gas chromatography (GC) × GC/TOF, Chang et al (2021) observed that the number of detected analytes increased with the number of structures that were damaged or destroyed. Principal component analysis was carried out for all features in both positive and negative modes (Supporting Information, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The features were then annotated with sample collection sites and storm events, and numbers of features for each sampling and reference sites are summarized in Table 1. No clear relationship was observed between overall numbers of features and levels of development or burned percentage (Supporting Information, Table S1), though in the companion study using gas chromatography (GC) × GC/TOF, Chang et al (2021) observed that the number of detected analytes increased with the number of structures that were damaged or destroyed. Principal component analysis was carried out for all features in both positive and negative modes (Supporting Information, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The sampling sites in Sonoma were located around Sonoma Creek, with the reference site located on the nearby Graham Creek tributary to Sonoma Creek. The watersheds of reference sites do not contain significant development (<0.05%), whereas wildfire‐impacted sites contain watersheds with a wide range of development (<1% in three cases and 3%–59% in the remaining seven cases; Chang et al, 2021). The city of Santa Rosa samples were collected only during the first storm event, and no specific reference site was sampled.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations